Ghosting in Emerging Adults' Romantic Relationships: The Digital Dissolution Disappearance Strategy. (December 2019) - LeFebvre, Leah E.; Allen, Mike; Rasner, Ryan D.; Garstad, Shelby; Wilms, Aleksander; Parrish, Callie
The purpose of this study is to examine relational dissolution using the technique of ghosting. This qualitative study explores the emerging adults' dissolution strategies leading up to and through enactment of disengagement through mediated contexts. Participants ( N = 99) completed questionnaires about their ghosting familiarity and participation as initiators or noninitiators. The majority of participants reported participating in both roles. Five themes described why initiators chose to enact ghosting, and three themes chronicled their ghosting decision-making processes. Noninitiators illustrated how they realized ghosting occurred through three themes. This exploratory investigation offers a definitive definition of ghosting and a modern discussion of its contents to dissolution, communication, and romantic relationship development.